Self-Reported SARS-CoV-2 Infections among National Blood Donor Cohort, United States, 2020–2022 - Bryan R. Spencer; Akintunde Akinseye; Eduard Grebe; Mars Stone; Karla G. Zurita; David J. Wright; James M. Haynes; Susan L. Stramer; Michael P. Busch (Emerging Infectious Diseases)
SARS-CoV-2 case surveillance in the United States did not distinguish first infections from reinfections. In a large blood donor cohort, self-reported first infections and reinfections during 2020–2022 mirrored public health case count surveillance, and reinfection incidence peaked in 2022. Blood donor data could aid in SARS-CoV-2 and emerging infectious disease surveillance.